The Effect of Nutrition Education for Athletes Using Video Media on The Knowledge and Nutrition Intake of Pencak Silat Athletes - Muslihatul Alawiyah; I Nyoman Adiyasa; Lalu Khairul Abdi; Lalu Juntra Utama; Suhaema Suhaema (Jurnal Gizi Prima (Prime Nutrition Journal), 2025)
Background: Nutrition education enhances athletic performance by improving knowledge and dietary intake. According to the Ministry of Youth and Sports, approximately 60% of athletes in Indonesia, including pencak silat athletes, have not received adequate nutrition education, leading to unplanned and unbalanced dietary patterns. Research Methods: This research employed a pre-experimental design with a one-group pretest-posttest approach. A total of 43 athletes were selected using purposive sampling. The intervention involved providing nutrition education through video media. Data were analysed using the Wilcoxon signed rank test. Research Result: There was an increase in athletes' nutrition knowledge, with the average pre-test score rising from 64.51 to 90.32. The Wilcoxon test showed a significant result with a p-value of 0.000 (p < 0.05). Additionally, there was an increase in the average energy intake by 714.20 kcal, protein by 9.86 grams, fat by 45.87 grams, and carbohydrates by 85.58 grams after the nutrition education. All changes were statistically significant (p = 0.000; p < 0.05). These findings indicate that nutrition education using video media effectively improves knowledge and nutrient intake among pencak silat athletes. Conclusion: Video media can be an efficient and applicable method for nutrition improvement programmes among athletes.